Population ecology size and habitat preference of the ghost orchid Didymoplexis pallens in Bogor Botanic Gardens, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Zulkarnaen RN, Garvita RV, Wawangningrum, H, Tyas KN. 2020. Population ecology size and habitat preference of the ghost orchid Didymoplexis pallens in Bogor Botanic Gardens, Indonesia. Biodiversitas 21: 2056-2061.  Didymoplexis pallens is a terrestrial orchid that has leafless characteristics. The population ecology of D. pallens is still not widely known because it only grows in certain areas and at certain times. This study aims to know the population ecology and habitat preference of D. pallens. The study was conducted in Bogor Botanic Gardens where D. pallens occurred naturally. The research method uses purposive sampling by establishing observation plots around bamboo collections in the garden. The results showed that D. pallens had a large population around specific bamboos, such as Gigantochloa verticillate, Gigantochloa atroviolacea and Dendrocalamus giganteus. In addition, the presence of D. pallens populations was strongly influenced by the presence of other plants that compete around it and light intensity. The Principal Component Analysis revealed there are two components of the abiotic factor that influenced the existence of D. pallens, i.e. the first component consisting of coverage, air humidity, temperature, and soil humidity. The second component consisting of litter thickness and soil pH.
Keywords: Didymoplexis pallens, ecological requirements, protected area, leafless orchid